HIF-1α/GPER signaling mediates the expression of VEGF induced by hypoxia in breast cancer associated fibroblasts (CAFs) - De Francesco, Ernestina Marianna; Lappano, Rosamaria; Santolla, Maria Francesca; Marsico, Stefania; Caruso, Arnaldo; Maggiolini, Marcello (Breast cancer research : BCR, 2013)
Introduction Carcinoma-associated fibroblasts (CAFs) play a pivotal role in cancer progression by contributing to invasion, metastasis and angiogenesis. Solid tumors possess a unique microenvironment characterized by local hypoxia, which induces gene expression changes and biological features leading to poor outcomes. Hypoxia Inducible Factor 1 (HIF-1) is the main transcription factor that mediates the cell response to hypoxia through different mechanisms that include the regulation of genes strongly associated with cancer aggressiveness. Among the HIF-1 target genes, the G-protein estrogen receptor (GPER) exerts a stimulatory role in diverse types of cancer cells and in CAFs. Methods We evaluated the regulation and function of the key angiogenic mediator vascular endothelial growth factor (VEGF) in CAFs exposed to hypoxia. Gene expression studies, Western blotting analysis and immunofluorescence experiments were performed in CAFs and breast cancer cells in the presence of cobalt chloride (CoCl 2) or cultured under low oxygen tension (2% O 2 ), in order to analyze the involvement of the HIF-1α/GPER signaling in the biological responses to hypoxia. We also explored the role of the HIF-1α/GPER transduction pathway in functional assays like tube formation in human umbilical vein endothelial cells (HUVECs) and cell migration in CAFs. Results We first determined that hypoxia induces the expression of HIF-1α and GPER in CAFs, then we ascertained that the HIF-1α/GPER signaling is involved in the regulation of VEGF expression in breast cancer cells and in CAFs exposed to hypoxia. We also assessed by ChIP assay that HIF-1α and GPER are both recruited to the VEGF promoter sequence and required for VEGF promoter stimulation upon hypoxic condition. As a biological counterpart of these findings, conditioned medium from hypoxic CAFs promoted tube formation in HUVECs in a HIF-1α/GPER dependent manner. The functional cooperation between HIF-1α and GPER in CAFs was also evidenced in the hypoxia-induced cell migration, which involved a further target of the HIF-1α/GPER signaling like connective tissue growth factor (CTGF). Conclusions The present results provide novel insight into the role elicited by the HIF-1α/GPER transduction pathway in CAFs towards the hypoxia-dependent tumor angiogenesis. Our findings further extend the molecular mechanisms through which the tumor microenvironment may contribute to cancer progression.